Glomerular filtration rate: compilation of some mathematical formulas used in pharmacokinetics and dosage - Vargas Mamani, Juan José (2021)
In the first part, an introduction of the meaning of the glomerular filtration rate was made, then the use of creatinine purification was defined, which is the most known method of measuring renal function, A summary was then made of the mathematical formulas for predicting the glomerular filtration rate divided into three groups, based on creatinine, cystatin C and inulin. The article continues with an explanation of the relationship between the rate of glomerular filtration and creatinine depuration in addition to mentioning its importance in the dosage, ends with a list of drugs whose excretion is mainly urinary and which are polar in nature.